Measurement and monitoring of nausea severity in emergency department patients: A comparison of scales and exploration of treatment efficacy outcome measures - Meek, R.; Egerton-Warburton, Diana; Mee, M.; Braitberg, G. (Blackwell Publishing Inc., 2015)
Objectives The objective was to investigate the correlation of the visual analog scale (VAS) and numeric rating scale (NRS) for nausea severity measurement and to explore options for improved reporting of antiemetic efficacy trial results. Methods This was a multicenter observational study of adult emergency department (ED) patients with nausea. Participants rated severity at enrollment and 30 minutes posttreatment using an adjectival scale, a VAS, and an NRS. Posttreatment, patients described symptom change and rated satisfaction. Results Ratings were performed by 258 patients. Both the VAS (0 to 100 mm) and the NRS (0 to 10) discriminated between adjectival severity categories. Median ratings with interquartile ranges (IQRs) were "severe" VAS 90.5 (IQR = 79 to 97) and NRS 9 (IQR = 8 to 9), "moderate" VAS 59 (IQR = 48 to 71) and NRS 6 (IQR = 5 to 7), "mild" VAS 34 (IQR = 25 to 49) and NRS 4 (IQR = 3 to 5), and "none" VAS 5 (IQR = 0 to 9) and NRS 0 (IQR = 0 to 1). Correlation between the VAS and NRS was high (0.83, Spearman). For the VAS, median mm (IQR) reductions for posttreatment change were "a lot less" -42 (IQR = -26 to -58.5), "a little less" -20.5 (IQR = -11 to -33), "the same" -2 (IQR = -8 to 3.5), "a little more" 14 (IQR = -2 to 22), and "a lot more" 17 (IQR = 6 to 23) and for satisfaction were "very satisfied" -45 (IQR = -27 to 63), "satisfied" -27 (IQR = -13 to 46), "unsure" -15 (IQR = -3 to -24), "dissatisfied" 4.5 (IQR = -5.5 to 13.5), and "very dissatisfied" 8.5 (IQR = 0 to 23). A VAS cutoff of =-5 mm detected symptom improvement with sensitivity 91.6% (95% CI = 86.7% to 95.1%), specificity 72.1% (95% CI = 59.9% to 82.3%), and positive predictive value 90.2% (95% CI = 85.1% to 94.0%). Conclusions The VAS and NRS correlate highly. A VAS cutoff level of =-5 mm was a good predictor of symptom improvement, suggesting that its inclusion as an outcome measure would enhance reporting in antiemetic efficacy trials.